Хронічна токсичність субстанції адамантан-1-амонієвої солі 2-(5-(адамантан-1-іл)-4-феніл-1,2,4-тріазол-3-ілтіо)оцтової кислоти - Одинцова, Віра Миколаївна; Абрамов, Андрій Володимирович; Бєленічев, Ігор Федорович (My University, 2016)
На сьогодні лише сім похідних адамантану пройшли клінічні випробування як лікарські засоби для лікування вульгарних вугрів, хвороби Альцгеймера, діабету 2-го типу, як противірусні. Інші знаходяться в стадії розробки як потенційні терапевтичні засоби для лікування захворювань, пов’язаних з перевантаженням залізом, малярії, туберкульозу, неврологічних та онкологічних захворювань, як антиоксидантні та протизапальні. Метою нашого дослідження було вивчення хронічної токсичності адамантан-1-амонієвої солі 2-(5-(адамантан-1-іл)-4-феніл-1,2,4-тріазол-3-ілтіо)оцтової кислоти для отримання інформації про синдроми токсичності та подальшого дослідження як потенційного лікарського засобу. Методи. Вивчення хронічної токсичності субстанції адамантан-1-амонієвої солі 2-(5-(адамантан-1-іл)-4-феніл-1,2,4-тріазол-3-ілтіо)оцтової кислоти проводились відповідно до вимог з доклінічного вивчення нових лікарських засобів. При виборі доз досліджуваної субстанції керувалися даними доклінічних досліджень специфічної активності та результатів визначення ОД50 і ЛД50. Nowadays, only seven adamantane derivatives have passed clinical trials as remedies applied for treatment of acne vulgaris, Alzheimer's disease, type 2 diabetes, and as antiviral drugs. The other are on the development stage as potential therapeutic agents for the treatment of diseases caused by iron overload, malaria, tuberculosis, neurological and oncological diseases, and as antioxidant and anti-inflammatory agents. The aim of our research was to study chronic toxicity of adamantane-1-ammonium salt of 2-(5-(adamantane-1-yl)-4-phenyl-1,2,4-triazole-3-thio)acetic acid to obtain information on the toxicity syndrome and the further research as a promising drug. Methods. Chronic toxicity study of adamantane-1-ammonium salt of 2-(5-(adamantane-1-yl)-4-phenyl-1,2,4-triazole-3-thio)acetic acid substance was carried out in accordance to requirements concerning preclinical study of new drugs. While selecting the doses of the studied substance, we were guided by the data of preclinical studies of specific activity and results of SD50 and LD50 determination. The experimental animals were kept in a separate room and were randomly divided into groups of 7 animals. The animals had a standard diet, getting the additive throughout the experiment. The substance was administered in the form of aqueous suspension. The control group got purified water in the same volume. The animals didn’t receive any meal 16 hours before administration of the substance; they got the remedy and the placebo at the same time. Results. During the chronic experiment, no deaths of the rats and evidence toxicity manifestations were observed. Any deviations of appearance parameters, behavior, eating and drinking, connected with 2-(5-(adamantane-1-yl)-4-phenyl-1,2,4-triazole-3-thio)acetic acid use, were not observed. Also, no significant changes or side effects, connected with the substance administration, were found.
Keywords: випробування на хронічну токсичність; доклінічні дослідження; 1,2,4-триазол; адамантан; експерименти на тваринах; ліки; chronic toxicity studies; preclinical trials; 1,2,4-triazole; adamantine; experiments in animals; remedies